Electrocardiographic Left Ventricular Mass Trajectories and the Effects of Treatment in Patients at Different Stages of Hypertension - Fuchs, Flávio D.; Valter, Leonardo Krause; Tavares, Arthur Lacerda; Camilo, Beatriz Padoin; Whelton, Paul K.; Scala, Luiz C. N.; Vilela-Martin, José F.; Poli-de-Figueiredo, Carlos E.; Silva, Ricardo Pereira e; Gus, Miguel; Bortolotto, Luiz A.; Schlatter, Rosane P.; et al. (MDPI, 2025)
Background: The comparison of left ventricular mass (LVM) at different BP levels and the effects of antihypertensive drug treatment on LVM are unknown. Objective: To compare the LVM of individuals with prehypertension and Stage 1 hypertension and assess the effects of treatment on LVM at these stages of hypertension. Methods: We estimated LVM in the PREVER-Prevention trial using Sokolow–Lyon and Cornell voltage and voltage–duration products before and after randomization to 18 months of treatment with low doses of chlorthalidone and amiloride or placebo in adults with JNC 7 “prehypertension” (systolic BP [SBP] of 120–139 mm Hg and diastolic BP [DBP] of 80–89 mm Hg). Similarly, in the PREVER-Treatment trial, we assessed these indices before and after randomization to 18 months of treatment with the chlorthalidone/amiloride combination or losartan in adults with JNC 7 “stage 1” hypertension (140–159 mm Hg or DBP of 90–99 mm Hg). Results: At baseline, the participants in the stage I hypertension trial exhibited higher mean LVM indices than those in the prehypertension trial. In the PREVER-Prevention trial, those randomized to the chlorthalidone/amiloride combination experienced a significant reduction in Sokolow–Lyon LVM indices compared to placebo (p = 0.02). In the PREVER-Treatment trial, those randomized to the chlorthalidone/amiloride combination or losartan experienced a similar reduction in electrocardiographic LVM during the 18 months of treatment (p < 0.01). Conclusions: The institution of low-dose antihypertensive drug therapy in prehypertension and treatment of patients with stage 1 hypertension has the potential to interrupt the progress of hypertensive cardiomyopathy.
Keywords: blood pressure; Cornell product; electrocardiography; hypertension; left ventricular mass; S-L voltage; treatment